Self-Reported Fall and Associate Risk Factors Among Korean American Adults In Washington State - Yoon, Jihye (My University, 2016)
Falls are leading cause of injuries and mortality among older adults. With increasing life expectancies and continual rise in health care expense, prevalence and cost of falls will increase dramatically. Previous studies have identified multiple risk factors that contribute to falls and fall related injuries however, not all older adults equally share these risk factors. There is a lack of research on Asian American fallers and to date, no study has examined falls among Korean Americans. To fill this gap in research, this thesis aims to examine the prevalence of self-reported falls and to identify associated risk factors of falls among Korean Americans adults in Washington State. Using an existing dataset from a previous study, self-reported falls and medical care due to falls were analyzed. The data comes from a 2013 population-based, cross-sectional survey and included the responses of 261 Korean American adults, aged 50 and older, residing in Seattle metropolitan area. The outcome variable is participants’ fall status within the past 12 months. Predictor variables are socio-demographic, health factors, acculturation, financial concerns for medical care costs, and medical tourism. Relationships between variables were examined using chi-square, bivariate, and multivariate logistic regression. In multivariate modeling, including marital status, household income, and current health status were significantly associated with fall. Unmarried participants were 2.65 (95% CI: 1.09-6.41) higher odds of falling compared to married. Participants with household income of $20,000 up to $39,999 were 4.62 (95% CI: 1.38-15.42) higher odds compared to income less than $20,000 and to income $40,000 or more. Participants who reported their health as fair and poor were 3.13 (98% CI: 1.36-7.19) higher odds compared to participants with good and excellent health. Characteristics of KAs who sought care for their fall were female (46.4% vs. 30.0%), older (75±10.9 vs. 67±11.78). The findings indicates that low income and fair or poor self-reported health were one of the key risk factors for fall among Korean Americans and highlight the needs for race specific fall strategies to reduce the burden of falls in all race group.
Thesis (Master's)--University of Washington, 2016-06
Keywords: Public health; health services